2007
DOI: 10.1159/000111133
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric Symptoms in Amnestic and Nonamnestic Mild Cognitive Impairment

Abstract: Background: The information regarding neuropsychiatric symptoms in the subtypes of mild cognitive impairment (MCI) is inadequate. Objective: To describe the behavioral neuropsychiatric symptoms of MCI in two subgroups of MCI patients with different neuropsychological characteristics. Methods: MCI patients are classified as amnestic (aMCI) if they have a prominent memory impairment, either alone or with other cognitive impairments (multiple domains with amnesia), or nonamnestic (naMCI) if a single nonmemory dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
77
2
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(92 citation statements)
references
References 59 publications
9
77
2
4
Order By: Relevance
“…As previously demonstrated, psychobehavioral symptoms are often present in the earlier phases of dementia due to neurodegenerative processes [35]. Moreover, previous studies [36,37] demonstrated that anxiety, depression and apathy are the disturbances more frequently found in the earliest phases of AD.…”
Section: Discussionmentioning
confidence: 85%
“…As previously demonstrated, psychobehavioral symptoms are often present in the earlier phases of dementia due to neurodegenerative processes [35]. Moreover, previous studies [36,37] demonstrated that anxiety, depression and apathy are the disturbances more frequently found in the earliest phases of AD.…”
Section: Discussionmentioning
confidence: 85%
“…Individuals with multiple-domain MCI experienced a similar frequency of depressive symptoms to individuals with Alzheimer's disease, which is greater than older people with normal cognitive functioning, although the symptoms were likely to be milder . One study showed that more individuals with non-amnestic MCI than individuals with the amnestic subtype of MCI had depressive symptoms, (Johnson et al, 2012) whereas another reported there were similar levels of symptoms of depression and anxiety for the amnestic and non-amnestic subtypes (Rozzini et al, 2008).…”
Section: Author (Year)mentioning
confidence: 99%
“…Наиболее типично наличие зрительных галлюцинаций для деменции с тельцами Леви. Галлюцинации наблюдаются и на стадии умеренных КН не-амнестического типа [40].…”
unclassified